2018
DOI: 10.1103/physrevapplied.9.054029
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Structure of Metal Whiskers

Abstract: We present TEM images of the interior of metal whiskers (MW) grown on electroplated Sn films. Along with earlier published information, our observations focus on a number of questions, such as why MWs' diameters are in the micron range (significantly exceeding the typical nano-sizes of nuclei in solids), why the diameters remain practically unchanged in the course of MW growth, what is the nature of MW diameter stochasticity, and what is the origin of the well-known striation structure of MW side surfaces. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…It explains as well the imperfect MWs cross sections, and the presence of striations on their side surfaces. 7 Earlier, it was observed indeed that the morphology of the whiskers was a result of whether they had nucleated on a single grain or on multiple grains. In the latter case, the whisker surface was fluted or striated.…”
Section: A Log-normal Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…It explains as well the imperfect MWs cross sections, and the presence of striations on their side surfaces. 7 Earlier, it was observed indeed that the morphology of the whiskers was a result of whether they had nucleated on a single grain or on multiple grains. In the latter case, the whisker surface was fluted or striated.…”
Section: A Log-normal Statisticsmentioning
confidence: 99%
“…Remarkably, that same scenario was recently put forward in order to explain the observed evidence of multifilament structure of MWs. 7 It is based on the electrostatic concept, according to which, MWs grow on local spots exhibiting significant enough surface charge density and its corresponding normal component of the electric field. The charging is related to various surface imperfections, such as a 'wrong' grain orientations, contaminations, deformations, etc.…”
Section: A Log-normal Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influencing factors include but are not limited to substrate, preparation method, and cultivation condition 5,6 Meanwhile, Sn whiskers have been observed to grow within days in some cases, while there are also some whiskers with an incubation period up to years and even decades. [7][8][9][10] Although many growth mechanisms have been proposed to explain the whiskering phenomenon, including a dislocation-based mechanism, 11,12 recrystallization mechanism, 13 compressive stress mechanism, 14,15 electrostatic mechanism, 16 and interface energy-driven mechanism, 17,18 the conclusions are still inconsistent, even contradictory [19][20][21] Among these mechanisms, the compressive stress mechanism is the most recognized one. However, although the acceleration of compressive stress on Sn whisker growth has been reported in many studies, [22][23][24][25] there are still many results inconsistent with the compressive stress mechanism, such as the whiskering phenomenon under tensile stress, 19 and the great growth rate difference under the same compressive stress level.…”
Section: Introductionmentioning
confidence: 99%
“…They found that electric charges generated in the insulating glass substrate under the Sn thin film were perpendicular to the Sn film, thus resulted in electrostatically driven whisker growth. Bora and Georgive [28] investigated only the morphology of tin whiskers grown out from Sn thin-film on Cu substrate by FIB-facilitated TEM images. They found that the whiskers consisted of multiple filaments whose individual radii are in the range of tens of nanometers.…”
Section: Introductionmentioning
confidence: 99%